Short-term effect of adhesive system on clinical performance of bulk fill composite - Vanessa Cristiane Araújo Oliveira; Fernanda Piana Santos Lima de Oliveira; Claudia Silami Magalhães; Fabíola Belkiss Santos de Oliveira; Isabella Pereira Marques; Mayara dos Santos Noronha; João Gabriel Souza; Daniela Araújo Veloso Popoff (Universidade Estadual de Campinas, 2021)
Aim: Although bulk fill composites have been widely used as restorative material, there is no consensus regarding the best clinical protocol in terms of composite technique and adhesive system. Therefore, this clinical trial evaluated the clinical performance of bulk fill composites for class I restorations under different protocols. Methods: A randomized clinical trial including 155 class I restorations was conducted using different adhesive systems: conventional technique (phosphoric acid + conventional three-step adhesive system) (Group 1, 2 and 3); or self-etching adhesive system (Groups 4, 5 and 6). Control groups 1 and 4 were restored with conventional composite; groups 2 and 5 with low viscosity bulk fill and conventional composite as occlusal coverage; groups 3 and 6 with high viscosity bulk fill. The FDI criteria was used for clinical evaluation at baseline and after 6 months. Results: All groups showed good clinical performance. At baseline, the adhesive system did not affect postoperative hypersensitivity. After 6 months, group 5 showed a significant reduction in color and translucency; group 6 a reduction in terms of anatomical form and for postoperative sensitivity and an improvement in patient satisfaction (p<0.05). Considering the same restorative technique, the use of the self-etching adhesive system showed a significant decrease in color and translucency (p<0.05). Conclusion: All groups showed favorable clinical performance, and promising results were found for the conventional adhesive system and high viscosity bulk fill protocol.